Clinical validation of the BREAST-Q breast-conserving therapy module - Stolpner, Ilona; Heil, Jörg; Feißt, Manuel; Karsten, Maria Margarete; Weber, Walter P.; Blohmer, Jens-Uwe; Forster, Tobias; Golatta, Michael; Schütz, Florian; Sohn, Christof; Hennigs, André (Annals of surgical oncology, 2019)
The BREAST-Q is a patient-reported outcome measure to evaluate satisfaction and health-related quality of life (HRQOL) after breast surgery. The aim of this study is to test the acceptability, reliability, and validity of the most recently developed BREAST-Q module for breast-conserving therapy (BCT) in a prospective clinical cohort.
Published: 21 May 2019
Gesehen am 21.04.2020